Pengaruh Kepercayaan Pelayanan, Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Pelanggan di Kantor Kelurahan Jeruk Kecamatan Lakarsantri Kota Surabaya - Keenan, Ravi; Ida Bagus Cempena (Nirta Learning Centre, 2025)
Abstract. This study aims to examine and analyze the effect of Service Trust, Service Quality, and Facilities on Customer Satisfaction. The research was conducted among customers of the Jeruk Sub-district Office, Lakarsantri Sub-district, City of Surabaya. A total of 100 respondents were sampled using questionnaires, and the analytical techniques applied included Validity Tests, Reliability Tests, Multiple Linear Regression, and Classical Analysis Tests using SPSS 25.The results of the study indicate that all indicators are valid and reliable. Based on the Multiple Linear Regression Test, the Facility variable has a more dominant influence, while the Service Quality variable has a lower impact. The T-Test results show that Trust in Quality has a significant partial effect on Customer Satisfaction, Service Quality has a partial but insignificant effect on Customer Satisfaction, and Facilities have a significant partial effect on Customer Satisfaction at the Jeruk Subdistrict Office in Lakarsantri District, Surabaya City. The F-Test results indicate that Trust in Service, Service Quality, and Facilities simultaneously have a significant effect on Customer Satisfaction at the Jeruk Subdistrict Office in Lakarsantri District, Surabaya City. Meanwhile, the Coefficient of Determination Test (R²) shows that the independent variables influence the dependent variable by 34.9%, while the remaining 65.1% is influenced by other variables outside the research model. Keywords: Service Trust; Service Quality; Facilities; Customer Satisfaction.